STUDY ANALYSIS OF PUBLIC TRANSPORT SELECTION BY STUDENTS IN TONDANO - Grace Sumakul; Supriyanto (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
Public transportation is one of the needs of the community, including students, to help with daily activities. This study aims to examine the selection of public transportation by students using descriptive analysis. Variables such as gender, age, price and quality of service are studied. Research shows that the majority of students still use public transportation and are not affected by the rise of online transportation. Female students prefer public transportation because it is more convenient. Those in the lower semesters use public transportation more because it is efficient. The price paid by students is in accordance with local regulations and what students want. The quality of service received is considered good so that students do not switch to other transportation